Inverter Current Feedback Control Of A Multilevel Inverter Controlling An Induction Motor Drive - et. al., Gayatri Mohapatra, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
An attempt is made to control the current of a PV integrated three-phase Cascaded H Bridge inverter, connected to a three-phase load with a matrix converter. The controller is designed to control the current and maintain the load power constant at any point of the disturbance enabling suitable control methods like PR controller {using the concept of inverter-current feedback (ICF)} and PI controller. A Matlab Simulink model of the said system is developed with suitable switching angles of the inverter switch selected using Differential Evolutional Algorithms (DEA). All the converters are modeled using a small scale averaging method to tune the controller. A novel controller technique of Matrix converter based multilevel inverter is proposed with the Proportional Resonant (PR) controller to control the power and the results are compared with the PI regulator. The ICF helps the PR controller to adjust the reference current and generate suitable control signal which is useful in reducing the harmonic content of the signal and hence a less distorted signal is produced during transients